2011
DOI: 10.1093/rheumatology/ker335
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Class II human leucocyte antigens in Italian and Spanish systemic sclerosis

Abstract: We describe multiple robust associations between SSc and HLA Class II antigens in Caucasoids that may help to understand the genetic architecture of SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 28 publications
5
32
0
Order By: Relevance
“…However, for the Hispanic populations, HLA-DRB1*1104 was the allele that showed the most significant association and the highest OR for this autoantibody. Interestingly, previous studies have also correlated HLA-DRB1*11 with ATA-positive status in whites, blacks and Hispanics [11,21,22]. The analyses performed in the ACA-positive subset of patients revealed an over-representation of the HLA-DQB1*0501 and HLA-DQB1*26 epi alleles in white population.…”
Section: Hlamentioning
confidence: 68%
See 1 more Smart Citation
“…However, for the Hispanic populations, HLA-DRB1*1104 was the allele that showed the most significant association and the highest OR for this autoantibody. Interestingly, previous studies have also correlated HLA-DRB1*11 with ATA-positive status in whites, blacks and Hispanics [11,21,22]. The analyses performed in the ACA-positive subset of patients revealed an over-representation of the HLA-DQB1*0501 and HLA-DQB1*26 epi alleles in white population.…”
Section: Hlamentioning
confidence: 68%
“…The analyses performed in the ACA-positive subset of patients revealed an over-representation of the HLA-DQB1*0501 and HLA-DQB1*26 epi alleles in white population. Additionally, significant associations with HLA-DRB1*01, HLA-DRB1*04 and HLA-DRB1*08 have also been reported [11,21,22]. The anti-RNA polymerase III antibody positive SSc patient subset was explained by HLA-DRB1*0404, HLA-DRB1*11 and HLA-DQB1*03 in Caucasian and Hispanic populations [20].…”
Section: Hlamentioning
confidence: 87%
“…Moreover, these HLA alleles not only determine SSc susceptibility, several studies also showed that some of them have a protective effect. It should also be noted that these associations can be common in different ethnicities, while others are specific to certain populations [24, 25]. The first GWAS in SSc reported that a SNP located in HLA-DQB1 had the strongest association [18].…”
Section: Genetic Involvementmentioning
confidence: 99%
“…Class I (HLA A, B, and C) and class II (HLA DR, DQ, and DP) molecules are expressed on the cell surface and participate in antigen presentation and T lymphocyte activation. Class I molecules also activate natural killer (NK) cell receptors [11], and class II molecules appear to stimulate the secretion of IL-6 and monocyte chemotactic protein (MCP-1) by fibroblasts, especially in antibody antitopoisomerase (ATA) associated clinical forms [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Caucasian patients were associated with HLA-DR5 [2325], corresponding to DRB1*05, and Japanese patients were associated with HLA-DR2 [5], DRB1*15, or DRB1*16 in the current nomenclature. The anticentromere antibody (ACA) was related to the HLA-DRB1*01, DRB1*04, DQA1*0101, and DQB1*0501 alleles [7, 12, 13, 23]. …”
Section: Introductionmentioning
confidence: 99%